A starting note: A historical perspective in Lasso - Mehmet Caner (International Econometric Review (IER), 2021)
In this note, I will look at history of Lasso estimation, which is the benchmark high dimensional estimation technique. I want to also give a perspective where Lasso may be evolving.
Keywords: C1; C5; C7; 330